Who trusts Berlusconi? An econometric analysis of the role of television in the political arena - Fabio Sabatini (Economics and Econometrics Research Institute (EERI), 2011)
This paper contributes to the literature by carrying out the first econometric investigation into the role of television in the formation of political consensus in Italy. Based on probit and instrumental variables estimates, we find trust in television to be the most significant predictor of trust in the Italian prime minister. The latter is also strongly and negatively correlated with trust in the judicial system and tolerance towards immigrants.
Keywords: D72; D83; H8; L82; Z1; Z13; 330; Trust; institutions; democracy; television; media; social capital; Italy; instrumental variables